2019
DOI: 10.3389/fenvs.2019.00022
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Glyphosate and Fluridone Concentrations in Water Column and Sediment Leachate

Abstract: Purpose: In recreational water bodies, herbicides are widely used for controlling unwanted weeds, and impacts of herbicide residues on health risks to aquatic ecosystem is a serious concern. This study was aimed to improve the existing understanding of the deposition of herbicides from water column to bed sediment and leachate of herbicides from bed sediment to water column. We investigated the attachment of two herbicides with sediment and release from sediment: (1) Glyphosate; and (2) Fluridone. The goal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Field assessments have revealed elevated sediment concentrations of fluridone and diquat compared to the water, by up to an order of magnitude (Hosea 2005), and similar results for fluridone have been observed in recent monitoring at both treated and untreated Delta sites (Rasmussen et al 2020). These field observations are consistent with laboratory evaluations that compare fluridone and glyphosate concentrations in sediment leachate: glyphosate concentrations in sediment diminish rapidly after initial washes; fluridone concentrations remain high after consecutive washes (Pandey et al 2019). Further study has shown that degradation of sediment-bound fluridone is faster with increasing exposure to ultra-violet light, increasing temperature (greater than 20 °C), and higher clay content in the sediment matrix (Wickham et al 2020).…”
Section: Non-target Effects Of Sav and Fav Control Measuressupporting
confidence: 83%
“…Field assessments have revealed elevated sediment concentrations of fluridone and diquat compared to the water, by up to an order of magnitude (Hosea 2005), and similar results for fluridone have been observed in recent monitoring at both treated and untreated Delta sites (Rasmussen et al 2020). These field observations are consistent with laboratory evaluations that compare fluridone and glyphosate concentrations in sediment leachate: glyphosate concentrations in sediment diminish rapidly after initial washes; fluridone concentrations remain high after consecutive washes (Pandey et al 2019). Further study has shown that degradation of sediment-bound fluridone is faster with increasing exposure to ultra-violet light, increasing temperature (greater than 20 °C), and higher clay content in the sediment matrix (Wickham et al 2020).…”
Section: Non-target Effects Of Sav and Fav Control Measuressupporting
confidence: 83%
“…Herbicides are predominantly utilised in agricultural activities, but substantial quantities are also utilised in forestry, industrial areas, public areas, parks, golf courts, and sports grounds for weed control and maintenance [ 5 , 6 ]. Pandey et al [ 45 ] also stated that these herbicides can be used to control invasive plants in water. As a result, the presence of these herbicides in dams/reservoirs may be attributed to their use to control aquatic weeds, such as algae and submerged weeds.…”
Section: Resultsmentioning
confidence: 99%
“…For phytoplankton and free-living submerged aquatic plants, water is the main medium through which they are exposed to dissolved herbicides. Resuspension of sediments contaminated with herbicides can result in the release of herbicides into the water column (Pandey et al 2019). Resuspension can therefore also expose phytoplankton and free-living aquatic plants indirectly to herbicides accumulated in the sediment.…”
Section: Exposure Of Aquatic Primary Producers To Herbicidesmentioning
confidence: 99%
“…Many herbicides interact with the dissolved and particulate organic matter in the water, resulting in the adsorption of active herbicides (Voice and Weber 1983;Chefetz et al 2004;Pandey et al 2019). These aggregates may sink to the bottom causing the transport of herbicides from the water column to the sediment.…”
Section: Fate Of Herbicides In the Aquatic Environmentmentioning
confidence: 99%